2019
DOI: 10.1515/rebs-2019-0085
|View full text |Cite
|
Sign up to set email alerts
|

The consumer explained from the perspective of the extended self

Abstract: Although the extended self is a relatively new concept, over the years it has developed rapidly, being the subject of study of several marketing researches. Our possessions contribute to reflecting our identity, so it is very important to look at how people expand their self in relation to others and how possessions become part of themselves. We can not hope to understand the behavior of consumers without first gaining a certain understanding of the attention they give to their possessions. The main findings u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…These two schools of thought regarding the positive and negative impacts of the globalization phenomenon appear to be polarized by different ideological and philosophical standings that have generated vigorous debates over the years. This perhaps explains why Lee (2000) and Manolica and Roman (2012) have laid claim to the fact that no single acceptable scholarly definition of the term has been reached as yet, following the over-polarization of the concept.…”
Section: Benefits and Discontentsmentioning
confidence: 99%
“…These two schools of thought regarding the positive and negative impacts of the globalization phenomenon appear to be polarized by different ideological and philosophical standings that have generated vigorous debates over the years. This perhaps explains why Lee (2000) and Manolica and Roman (2012) have laid claim to the fact that no single acceptable scholarly definition of the term has been reached as yet, following the over-polarization of the concept.…”
Section: Benefits and Discontentsmentioning
confidence: 99%
“…Wu and Zhao (2021) have found that value consciousness has a positive impact and that perceived social risk harms the purchase intention of counterfeit luxury products. Manolica, Cluci, and Roman (2021) discussed that the concept of self has become prevalent due to digital possessions and social media. Wang (2019) has found that self-concept is a key factor that can help understand consumers' counterfeit purchase intentions.…”
Section: Counterfeit Consumptionmentioning
confidence: 99%
“…The concept of globalization evokes varied understandings and interpretations (Burlacu et al, 2018;Manolica & Roman, 2012). For instance, while some scholars relate the phenomenon to the shrinking of 'time' and 'space', others associate the phenomenon with the exploitation of the developing world by giant economic nations.…”
mentioning
confidence: 99%